PERBEDAAN PUTUSAN PRAPID P.N. TARUTUNG NO. 6/PID.PRA/2020 DAN PUTUSAN PRAPID P.N. MEDAN NO. 5/PID.PRA/2021 - Jenda Riahta Silaban; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (Universitas Dharmawangsa, 2023)
ABSTRACTDecision of the Constitutional Court of the Republic of Indonesia No. 21/PUU-XII/2014,date. 28/04/2015, expanded the prepid object regarding